A porous Ni3N nanosheet array as a high-performance non-noble-metal catalyst for urea-assisted electrochemical hydrogen production. Issue 7 (16th May 2017) - Liu, Qin; Xie, Lisi; Qu, Fengli; Liu, Zhiang; Du, Gu; Asiri, Abdullah M.; Sun, Xuping
Abstract : The porous Ni3 N NA/CC acts as a high-performance and durable electrocatalyst for urea oxidation needing a potential of 1.35 V to drive 10 mA cm −2 water-splitting current in 1.0 M KOH with 0.33 M urea. Abstract : Developing highly efficient and non-noble-metal catalysts is of great importance for electrochemical energy storage and conversion. In this communication, we report the development of a porous Ni3 N nanosheet array on carbon cloth (Ni3 N NA/CC) as a high-performance and durable electrocatalyst for urea oxidation. To drive 10 mA cm −2, this Ni3 N NA/CC only demands a potential of 1.35 V in 1.0 M KOH with 0.33 M urea. The high catalytic activity of the hydrogen evolution reaction enables Ni3 N NA/CC as a bifunctional catalyst electrode for electrochemical hydrogen production and the two-electrode electrolyzer is capable of offering 10 mA cm −2 at a cell voltage of only 1.44 V, 120 mV less than that for the urea-free counterpart.